2019
DOI: 10.1113/jp277793
|View full text |Cite
|
Sign up to set email alerts
|

Precapillary pulmonary gas exchange is similar for oxygen and inert gases

Abstract: Key points Precapillary gas exchange for oxygen has been documented in both humans and animals. It has been suggested that, if precapillary gas exchange occurs to a greater extent for inert gases than for oxygen, shunt and its effects on arterial oxygenation may be underestimated by the multiple inert gas elimination technique (MIGET). We evaluated fractional precapillary gas exchange in canines for O2 and two inert gases, sulphur hexafluoride and ethane, by measuring these gases in the proximal pulmonary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The first Swan-Ganz catheter (7fr, 2.3 mm) was positioned approximately 1-2 cm distal to the right ventricular/pulmonary artery interface as confirmed by direct pressure monitoring, and was used for mixed venous sampling and pressure monitoring. Another Swan-Ganz catheter (5fr, 1.7 mm) was positioned approximately 1 cm proximal to the wedge position, also confirmed by direct pressure monitoring, and was part of a separate study not reported here (Stickland et al 2019).…”
Section: Instrumentationmentioning
confidence: 80%
See 3 more Smart Citations
“…The first Swan-Ganz catheter (7fr, 2.3 mm) was positioned approximately 1-2 cm distal to the right ventricular/pulmonary artery interface as confirmed by direct pressure monitoring, and was used for mixed venous sampling and pressure monitoring. Another Swan-Ganz catheter (5fr, 1.7 mm) was positioned approximately 1 cm proximal to the wedge position, also confirmed by direct pressure monitoring, and was part of a separate study not reported here (Stickland et al 2019).…”
Section: Instrumentationmentioning
confidence: 80%
“…regions whereVA/Q = 0.005-0.1) with any of the interventions, suggesting that when recruited, IPAVAs do not appear to function as regions of lowVA/Q ratio. Alternately, as discussed in our companion paper (Stickland et al 2019) these may be so low that MIGET cannot distinguish these regions from shunt.…”
Section: Gas Exchangementioning
confidence: 91%
See 2 more Smart Citations